(untitled) (Research, Society and Development, 2023)
Objective: To analyze the main approaches to socioeconomic impacts on family planning due to teenage pregnancy. Methodology: In this study, we chose to carry out a narrative review of the literature to identify the studies carried out on teenage pregnancy, designated for adolescents aged 12 to 18 years, its causes and consequences and the actions of the health team in preventing pregnancy unplanned in adolescence. Results And Discussion: Nine articles were selected from the Scientific Electronic Library online platform (Scielo), six from the Latin American and Caribbean Health Sciences Literature (LILACS) and 16 from the Medical Literature Analysis and Retrieval System Online (Medline). In addition to social repercussions and on the health of the pregnant woman, they also portrayed the harm to newborns. Conclusion: The importance of preventing teenage pregnancy, which is most often unwanted and has negative consequences for the adolescent, child and family context. The study allowed us to understand as main factors for teenage pregnancy the vulnerable financial situation, low education, black or brown race, lack of a father figure, and, with family history of mother also with teenage pregnancy.